Ammonium perchlorate compound based on Pickering emulsion template method, synthetic method and application

The construction of ammonium perchlorate composite was solved by the Pickering emulsion template method, which solved the problem of poor dispersion performance of nanocatalysts in solid propellants, achieved efficient catalytic effects, and significantly improved the combustion performance and safety performance of solid propellants.

CN119613207APending Publication Date: 2025-03-14XIAN MODERN CHEM RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411644888.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the dispersion performance of nano-scale catalysts in solid propellants is poor, resulting in poor contact with ammonium perchlorate oxidant, and the combustion performance of the solid propellants cannot be effectively improved.

Method used

The ammonium perchlorate composite was constructed by the Pickering emulsion template method, and the surface-modified nanoemulsifier was stabilized at the oil-water interface, promoting the dispersion and efficient contact of the nanocatalysts, forming an efficient catalytic system.

Benefits of technology

The effective dispersion and efficient contact of nanocatalysts are achieved, which significantly improves the combustion performance of solid propellants, reduces the amount of catalyst used, and improves the mechanical and safety performance of propellants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613207A_ABST
    Figure CN119613207A_ABST
Patent Text Reader

Abstract

The invention provides an ammonium perchlorate compound based on a Pickering emulsion template method as well as a synthesis method and application of the ammonium perchlorate compound. The preparation method comprises the following steps: selecting a nano catalyst with relatively good catalytic activity on ammonium perchlorate, performing surface modification on the nano catalyst to serve as a Pickering emulsion stabilizer, taking deionized water for dissolving the ammonium perchlorate as an emulsion water phase, taking ethyl acetate and dichloromethane dispersion liquid for dispersing a nano emulsifier as an emulsion oil phase, and mixing the water phase and the oil phase to prepare the Pickering emulsion. And preparing the Pickering emulsion under the action of ultrasonic or high-speed shearing. The ammonium perchlorate compound is constructed by adopting a Pickering emulsion template method, and after the nano emulsifier is embedded on the surface of the ammonium perchlorate, the morphology control of the ammonium perchlorate is facilitated while the catalytic combustion performance of the nano emulsifier is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid propellants, and relates to ammonium perchlorate, an oxidant of solid propellants, and specifically relates to an ammonium perchlorate complex based on a Pickering emulsion template method, a synthesis method and an application thereof. Background Art

[0002] Solid propellant is the power source of rocket and missile engines, and its combustion performance is closely related to the combat effectiveness and survivability of missile weapons. Therefore, the regulation of solid propellant combustion performance has become one of the key technologies that restrict weapon performance, and the use of combustion catalysts is one of the most effective and direct means of regulating combustion performance. At present, the combustion catalysts used in solid propellants are mostly micrometer-scale. Due to the small number of active sites, low utilization rate, and large usage, it is increasingly difficult to meet the performance requirements of my country's missile weapons for propellant charges.

[0003] Nanocatalysts have a high specific surface area, which allows them to provide more active sites during catalytic combustion and show good application potential. However, the high surface energy makes them easy to agglomerate, and the catalytic activity is significantly reduced after agglomeration. In addition, in the physical mixing process of existing composite propellants, nanocatalysts cannot be effectively dispersed, the contact between nanocatalysts and oxidants is poor, and the catalytic activity of nanomaterials cannot be exerted.

[0004] Pickering emulsion is an emulsion system in which a solid particle stabilizer is dispersed in an oil-water phase. Compared with traditional emulsions, Pickering emulsion has the advantages of strong interface stability, renewability, low toxicity and low cost. It has been widely used in industries such as cosmetics, food, pharmaceuticals, petroleum and wastewater treatment, but is rarely used in the field of solid propellants. Summary of the invention

[0005] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to provide an ammonium perchlorate complex, a synthesis method and an application based on the Pickering emulsion template method, so as to solve the technical problem in the prior art that the nanoscale catalyst has poor dispersion performance in the solid propellant and weak reaction with the ammonium perchlorate oxidant, resulting in poor combustion performance of the solid propellant.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:

[0007] An ammonium perchlorate complex based on a Pickering emulsion template method comprises an emulsifier and ammonium perchlorate; the emulsifier is a non-modified emulsifier or a modified emulsifier; the non-modified emulsifier is selected from one or more of nano metal oxides, graphene-metal oxide complexes, and graphene metal complexes; the modified emulsifier is selected from one or more of modified nano metal oxides, modified graphene-metal oxide complexes, and modified graphene metal complexes.

[0008] The present invention also has the following technical features:

[0009] Specifically, the nano metal oxide is selected from one or more of nano iron oxide, nano copper oxide, nano cobalt oxide and nano nickel oxide; the graphene-metal oxide composite is selected from one or more of graphene-iron oxide composite, graphene-copper oxide composite, graphene-cobalt oxide composite and graphene-nickel oxide composite; the graphene metal complex is selected from one or more of graphene-ferrocene complex, graphene-Schiff base iron complex and graphene-organic acid iron complex;

[0010] Specifically, the modified nano metal oxide is selected from one or more of stearic acid-modified nano iron oxide, stearic acid-modified nano copper oxide, stearic acid-modified nano cobalt oxide, stearic acid-modified nano nickel oxide, silane coupling agent-modified nano iron oxide, silane coupling agent-modified nano copper oxide, silane coupling agent-modified nano cobalt oxide and silane coupling agent-modified nano nickel oxide; the modified graphene-metal oxide composite is selected from stearic acid-modified graphene-iron oxide composite, stearic acid-modified graphene-copper oxide composite, stearic acid-modified graphene-cobalt oxide composite, stearic acid-modified graphene-nickel oxide composite. , a silane coupling agent modified graphene-iron oxide complex, a silane coupling agent modified graphene-copper oxide complex, a silane coupling agent modified graphene-cobalt oxide complex and a silane coupling agent modified graphene-nickel oxide complex; the modified graphene metal complex is selected from one or more of stearic acid modified graphene-ferrocene complex, stearic acid modified graphene-Schiff base iron complex, stearic acid modified graphene-organic acid iron complex, silane coupling agent modified graphene-ferrocene complex, silane coupling agent modified graphene-Schiff base iron complex and silane coupling agent modified graphene-organic acid iron complex.

[0011] Specifically, the mass ratio of the emulsifier to ammonium perchlorate is 1:(10-10000).

[0012] Specifically, the ammonium perchlorate complex consists of a Pickering emulsion oil phase and a Pickering emulsion water phase; the Pickering emulsion oil phase consists of an emulsifier and a non-aqueous solvent; the Pickering emulsion water phase consists of ammonium perchlorate and water; and the non-aqueous solvent is selected from one or more of ethyl acetate, dichloromethane and toluene.

[0013] Specifically, the volume ratio of the Pickering emulsion oil phase to the Pickering emulsion water phase is (1-5): (1-5).

[0014] Specifically, the particle size of the nano metal oxide is 10 to 30 nm.

[0015] The present invention also protects a method for synthesizing an ammonium perchlorate complex based on the Pickering emulsion template method as described above, the method comprising: ultrasonically dispersing a non-modified emulsifier or a modified emulsifier in a non-aqueous solvent to obtain a Pickering emulsion oil phase; dissolving ammonium perchlorate in water to obtain a Pickering emulsion water phase; mixing the Pickering emulsion oil phase and the Pickering emulsion water phase, and emulsifying at an emulsification rate of 15000 to 20000 rpm for 2 to 3 minutes to obtain the ammonium perchlorate complex.

[0016] Specifically, the preparation process of the modified emulsifier includes: ultrasonically dispersing a non-modified emulsifier in a solvent to obtain an emulsifier dispersion; dissolving a modifier in a solvent at 40 to 70° C. to obtain a modifier solution, wherein the modifier is stearic acid or a silane coupling agent; mixing the emulsifier dispersion with the modifier solution, reacting at 40 to 70° C. for 1 to 3 hours, and obtaining a modified emulsifier after centrifugation and washing.

[0017] Specifically, the solvent is ethanol.

[0018] The present invention also protects the use of the ammonium perchlorate complex based on the Pickering emulsion template method as an oxidant to partially replace ammonium perchlorate in composite propellants.

[0019] Specifically, calculated on a dry weight basis, the amount of the ammonium perchlorate complex based on the Pickering emulsion template method added to the composite propellant is 5 to 30 wt.%.

[0020] The beneficial technical effects of the present invention compared with the prior art are as follows:

[0021] (I) The present invention adopts the Pickering emulsion template method to construct an ammonium perchlorate complex, and uses a surface-modified nanocatalyst as an emulsifier for the Pickering emulsion. The nanoemulsifier is stable at the oil-water interface, and after solidification, it promotes the dispersion of the nanoscale catalyst, achieving efficient contact between the nanocatalyst and ammonium perchlorate, so that the nanocatalyst can give full play to its advantageous performance, thereby improving the combustion performance of the solid propellant. The ammonium perchlorate complex synthesized based on the Pickering emulsion template method can replace part of the ammonium perchlorate as a functional complex.

[0022] (II) The present invention adopts the Pickering emulsion template method to construct an ammonium perchlorate complex, which improves the combustion performance of the solid propellant while reducing the amount of catalyst used; in addition, the introduction of the graphene-based catalyst helps to reduce the sensitivity of the solid propellant, thereby helping to improve the mechanical and safety properties of the solid propellant, and has good application potential in the field of solid propellants. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The invention is a technical route for the synthesis of ammonium perchlorate complex based on the Pickering emulsion template method.

[0024] Figure 2 This is a droplet morphology of the nano-iron oxide stabilized Pickering emulsion of Example 1.

[0025] Figure 3 This is a droplet morphology of the Pickering emulsion stabilized by the graphene-iron tannic acid complex of Example 2.

[0026] Figure 4 This is a droplet morphology of the Pickering emulsion stabilized by the stearic acid-modified graphene-Schiff base iron complex of Example 3.

[0027] Figure 5 This is a droplet morphology of the Pickering emulsion stabilized by the stearic acid-modified graphene-iron tannate complex of Example 4.

[0028] Figure 6 This is a droplet morphology of the stearic acid-modified nano-copper oxide-stabilized Pickering emulsion of Example 5.

[0029] Figure 7 is the differential scanning calorimetry curve of the cured ammonium perchlorate composite. DETAILED DESCRIPTION

[0030] The technical route of the present invention is as follows Figure 1 The specific technical ideas are as follows:

[0031] Based on the highly efficient catalyst of thermal decomposition and combustion of ammonium perchlorate (AP), nano metal oxides, graphene-metal oxide composites and graphene metal complexes can be selected as nano emulsifiers. Among them, nano metal oxides can be selected from nano iron oxide, copper oxide, cobalt oxide, and nickel oxide; graphene-metal oxide composites can be selected from graphene-iron oxide composites, graphene-copper oxide composites, graphene-cobalt oxide composites, and graphene-nickel oxide composites; graphene metal complexes can use graphene-ferrocene complexes, graphene-Schiff base iron complexes, and graphene-organic acid iron complexes.

[0032] Considering the hydrophilicity and hydrophobicity of the nanoemulsifier, the surface of the nanoemulsifier can be further modified by a modifier such as stearic acid or a silane coupling agent.

[0033] Considering that AP has good solubility in water, AP was dissolved in water to prepare AP aqueous solution as the aqueous phase of the Pickering emulsion; organic solvents incompatible with water, such as ethyl acetate, dichloromethane, and toluene, were selected as oil phase solvents, and nanoemulsifiers were ultrasonically dispersed therein to prepare the Pickering emulsion oil phase.

[0034] The prepared Pickering emulsion water phase and oil phase are mixed, the volume ratio of the water phase to the oil phase is between 5:1 and 1:5, and the mass percentage of the nanoemulsifier to the AP is between 0.001 and 0.1. The mixed solution is placed in a beaker, and a stable Pickering emulsion is prepared by ultrasound or high-speed shearing, the nanoemulsifier is dispersed at the oil-water interface, and the AP is in the water phase. The microspherical (O / W type) or porous (W / O type) ammonium perchlorate (AP) complex can be further prepared by solvent evaporation, freeze drying, spray granulation and other methods.

[0035] It should be noted that all raw materials used in the present invention, unless otherwise specified, are raw materials known in the art or raw materials synthesized and reported by the inventor's project, for example:

[0036] Graphene-Schiff base iron complex is a known complex in the prior art, which is recorded in the document Insight into graphene-salen metal nanocomposites on combustion performance and mechanism of HMX-CMDB propellant (M. Zhang, FQ Zhao, H. Li, ZF Yuan, S. Dong, Y. Wang, XL Chen, YJ Yang, XD Song, ZF Jiang,, Chem. Eng. J. 429 (2022) 132175.).

[0037] The graphene-iron tannate complex is a known complex in the prior art, which is recorded in the document Effects of graphene organic iron nanocomplex on the pyrolysis and laser ignition performance of TKX-50 (Ming Zhang, Fengqi Zhao, Hexin Liu, Na Li, Yifan Jiang, Zhen Zhang, Hui Li, Zhao Qin, Journal of Analytical and Applied Pyrolysis, 179 (2024) 106503).

[0038] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.

[0039] Embodiment 1:

[0040] This embodiment provides a method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method, the method comprising the following steps: ultrasonically dispersing nano-iron oxide with a diameter of 20 nm in an ethyl acetate solvent to obtain a Pickering emulsion oil phase, wherein the final concentration of the nano-iron oxide in the Pickering emulsion oil phase is 0.5 mg / mL; dissolving ammonium perchlorate (AP) in deionized water to obtain a Pickering emulsion water phase, wherein the final concentration of ammonium perchlorate in the Pickering emulsion water phase is 0.2 g / mL; taking 20 mL of the Pickering emulsion oil phase and 20 mL of the Pickering emulsion water phase, mixing them, and emulsifying them in a high-speed shear emulsifier at an emulsification rate of 20,000 rpm for 2 minutes to obtain an emulsion-like ammonium perchlorate complex.

[0041] In the ammonium perchlorate emulsion complex finally prepared in this example, the mass ratio of nano-iron oxide to AP is 1:400. Figure 2 This is a morphology image of the ammonium perchlorate complex droplet taken by optical microscopy. The emulsion can be further solidified to obtain an AP-based complex.

[0042] Embodiment 2:

[0043] The present embodiment provides a method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method, the method comprising the following steps: ultrasonically dispersing a graphene-tannic acid iron complex in a dichloromethane solvent to obtain a Pickering emulsion oil phase, wherein the final concentration of the graphene-tannic acid iron complex in the Pickering emulsion oil phase is 0.6 mg / mL; dissolving ammonium perchlorate (AP) in deionized water to obtain a Pickering emulsion water phase, wherein the final concentration of ammonium perchlorate in the Pickering emulsion water phase is 2 g / mL; mixing 10 mL of the Pickering emulsion oil phase and 10 mL of the Pickering emulsion water phase, and emulsifying the mixture in a high-speed shear emulsifier at an emulsification rate of 20,000 rpm for 3 min to obtain an emulsion-like ammonium perchlorate complex.

[0044] In the emulsion-like ammonium perchlorate complex finally prepared in this embodiment, the mass ratio of the hard graphene-iron tannic acid complex to AP is 3:10000. Figure 3 This is a droplet morphology image of the emulsion taken through an optical microscope. It can be seen that the emulsion has good stability and can be further cured by solvent evaporation and other curing methods to obtain an AP-based composite.

[0045] Embodiment 3:

[0046] This embodiment provides a method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method, the method comprising the following steps: ultrasonically dispersing 0.02 g of a stearic acid-modified graphene-Schiff base iron complex in 10 mL of a dichloromethane solvent to obtain a Pickering emulsion oil phase, wherein the final concentration of the stearic acid-modified graphene-Schiff base iron complex in the Pickering emulsion oil phase is 2 mg / mL; dissolving 0.6 g of ammonium perchlorate (AP) in 10 mL of deionized water to obtain a Pickering emulsion water phase, wherein the final concentration of ammonium perchlorate in the Pickering emulsion water phase is 0.06 g / mL; mixing the above 10 mL of the Pickering emulsion oil phase and 10 mL of the Pickering emulsion water phase, and emulsifying the mixture in a high-speed shear emulsifier at an emulsification rate of 20,000 rpm for 2 min to obtain an emulsion-like ammonium perchlorate complex.

[0047] In this embodiment, the preparation process of the stearic acid-modified graphene-Schiff base iron complex includes: ultrasonically dispersing the graphene-Schiff base iron complex in ethanol to obtain a graphene-Schiff base iron complex ethanol dispersion, wherein the final concentration of the graphene-Schiff base iron complex in the graphene-Schiff base iron complex ethanol dispersion is 1 mg / mL; dissolving stearic acid in ethanol at 55°C to obtain a stearic acid ethanol solution, mixing the above-prepared graphene-Schiff base iron complex ethanol dispersion with the stearic acid ethanol solution, wherein the mass of stearic acid is 10% of the graphene-Schiff base iron complex; then reacting at 55°C for 2h, and obtaining a stearic acid-modified graphene-Schiff base iron complex after centrifugation, ethanol washing, and drying.

[0048] In the ammonium perchlorate emulsion complex finally prepared in this example, the mass ratio of the stearic acid-modified graphene-Schiff base iron complex to AP is 1:30. Figure 4 The droplet morphology of the emulsion was taken by optical microscope after standing for 12 hours.

[0049] Embodiment 4:

[0050] This embodiment provides a method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method, the method comprising the following steps: ultrasonically dispersing 0.02 g of a stearic acid-modified graphene-tannic acid iron complex in 10 mL of a dichloromethane solvent to obtain a Pickering emulsion oil phase, wherein the final concentration of the graphene-tannic acid iron complex in the Pickering emulsion oil phase is 2 mg / mL; dissolving 0.6 g of ammonium perchlorate (AP) in 10 mL of deionized water to obtain a Pickering emulsion water phase, wherein the final concentration of ammonium perchlorate in the Pickering emulsion water phase is 0.06 g / mL; mixing the above 10 mL of the Pickering emulsion oil phase and 10 mL of the Pickering emulsion water phase, and emulsifying the mixture in a high-speed shear emulsifier at an emulsification rate of 15000 rpm for 3 min to obtain an emulsion-like ammonium perchlorate complex.

[0051] In this embodiment, the preparation process of the stearic acid modified graphene-tannic acid iron complex includes: ultrasonically dispersing the graphene-tannic acid iron complex in ethanol to obtain a graphene-tannic acid iron complex ethanol dispersion, wherein the final concentration of the graphene-tannic acid iron complex in the graphene-tannic acid iron complex ethanol dispersion is 1 mg / mL; dissolving stearic acid in ethanol at 55°C to obtain a stearic acid ethanol solution; mixing the above-prepared graphene-tannic acid iron complex ethanol dispersion with the stearic acid ethanol solution, wherein the mass of stearic acid is 10% of the graphene-tannic acid iron complex; then reacting at 55°C for 2h, and obtaining a stearic acid modified graphene-tannic acid iron complex after centrifugation, ethanol washing, and drying.

[0052] In the emulsion-like ammonium perchlorate complex finally prepared in this example, the mass ratio of the stearic acid-modified graphene-ferric tannate complex to AP is 1:30. Figure 5 The droplet morphology of the emulsion was taken by optical microscope after standing for 12 hours.

[0053] Embodiment 5:

[0054] This embodiment provides a method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method, which comprises the following steps: ultrasonically dispersing 0.05 g of stearic acid-modified nano-copper oxide in 10 mL of ethyl acetate solvent to obtain a Pickering emulsion oil phase, wherein the final concentration of stearic acid-modified nano-copper oxide in the Pickering emulsion oil phase is 5 mg / mL; dissolving 0.5 g of ammonium perchlorate (AP) in 10 mL of deionized water to obtain a Pickering emulsion water phase, wherein the final concentration of ammonium perchlorate in the Pickering emulsion water phase is 0.05 g / mL; mixing the above 10 mL of the Pickering emulsion oil phase and 10 mL of the Pickering emulsion water phase, and emulsifying the mixture in a high-speed shear emulsifier at an emulsification rate of 20,000 rpm for 2 min to obtain an emulsion-like ammonium perchlorate complex.

[0055] In this embodiment, the preparation process of stearic acid-modified nano copper oxide includes: ultrasonically dispersing 1g of nano copper oxide (Aladdin, 20nm) in 30mL of ethanol to obtain a nano copper oxide ethanol dispersion; dissolving 0.01g of stearic acid in 55°C ethanol (20mL) to obtain a stearic acid ethanol solution, mixing the above-prepared nano copper oxide ethanol dispersion with the stearic acid ethanol solution, reacting at 55°C for 2h, and obtaining stearic acid-modified nano copper oxide after centrifugation, ethanol washing, and drying.

[0056] In the ammonium perchlorate emulsion complex finally prepared in this example, the mass ratio of the stearic acid-modified nano-copper oxide to the ammonium perchlorate is 1:10. Figure 6 The droplet morphology of the emulsion was taken by optical microscope after standing for 12 hours.

[0057] Embodiment 6:

[0058] This example provides an application of the ammonium perchlorate complex prepared in Examples 1 to 4 as an oxidant to partially replace ammonium perchlorate in a composite propellant. The application comprises: curing the emulsion-like ammonium perchlorate complex prepared in Examples 1 to 4 at 50° C. for 24 hours to obtain a solid ammonium perchlorate complex.

[0059] In this example, the thermal decomposition performance of the solid ammonium perchlorate complex was studied. Figure 7 As shown. Figure 7 It can be seen from the curve S1 in Figure 1 that after being compounded with nano-iron oxide, the high-temperature decomposition peak temperature of ammonium perchlorate is significantly reduced from 404.3°C to 349.2°C. Figure 7 It can be seen from the curve S2 in that after being compounded with graphene-ferric tannate, the high-temperature decomposition peak temperature of ammonium perchlorate is significantly reduced from 404.3°C to 341.1°C. Figure 7 It can be seen from the curve S3 in Figure 1 that after being composited with the graphene-Schiff base iron modified with stearic acid, the high-temperature decomposition peak temperature of ammonium perchlorate is significantly reduced from 404.3°C to 351.2°C. Figure 7 It can be seen from curve S4 in that after being composited with graphene-iron tannate before and after stearic acid modification, the high-temperature decomposition peak temperature of ammonium perchlorate is significantly reduced from 404.3°C to 360.6°C.

[0060] It can be seen from the above results that, as the first step of combustion, the promotion of thermal decomposition of ammonium perchlorate helps it to decompose more quickly and completely in the propellant; after the ammonium perchlorate composite of the present invention is used in the solid propellant, the combustion performance of the solid propellant can be improved.

[0061] In this embodiment, the formula of the composite propellant is as follows:

[0062] Table 1. Composite propellant formula composition

[0063]

[0064]

Claims

1. An ammonium perchlorate complex based on the Pickering emulsion template method, characterized in that: Includes emulsifiers and ammonium perchlorate; The emulsifier is a non-modified emulsifier or a modified emulsifier; The non-modified emulsifier is selected from one or more of nano metal oxides, graphene-metal oxide composites, and graphene metal complexes; The modified emulsifier is selected from one or more of modified nano metal oxides, modified graphene-metal oxide composites, and modified graphene metal complexes.

2. The ammonium perchlorate complex based on the Pickering emulsion template method according to claim 1, characterized in that: The nano metal oxide is selected from one or more of nano iron oxide, nano copper oxide, nano cobalt oxide and nano nickel oxide; The graphene-metal oxide composite is selected from one or more of a graphene-iron oxide composite, a graphene-copper oxide composite, a graphene-cobalt oxide composite and a graphene-nickel oxide composite; The graphene metal complex is selected from one or more of a graphene-ferrocene complex, a graphene-Schiff base iron complex and a graphene-organic acid iron complex; The modified nano metal oxide is selected from one or more of stearic acid-modified nano iron oxide, stearic acid-modified nano copper oxide, stearic acid-modified nano cobalt oxide, stearic acid-modified nano nickel oxide, silane coupling agent-modified nano iron oxide, silane coupling agent-modified nano copper oxide, silane coupling agent-modified nano cobalt oxide and silane coupling agent-modified nano nickel oxide; The modified graphene-metal oxide composite is selected from one or more of a stearic acid-modified graphene-iron oxide composite, a stearic acid-modified graphene-copper oxide composite, a stearic acid-modified graphene-cobalt oxide composite, a stearic acid-modified graphene-nickel oxide composite, a silane coupling agent-modified graphene-iron oxide composite, a silane coupling agent-modified graphene-copper oxide composite, a silane coupling agent-modified graphene-cobalt oxide composite, and a silane coupling agent-modified graphene-nickel oxide composite; The modified graphene metal complex is selected from one or more of a stearic acid-modified graphene-ferrocene complex, a stearic acid-modified graphene-Schiff base iron complex, a stearic acid-modified graphene-organic acid iron complex, a silane coupling agent-modified graphene-ferrocene complex, a silane coupling agent-modified graphene-Schiff base iron complex, and a silane coupling agent-modified graphene-organic acid iron complex.

3. The ammonium perchlorate complex based on the Pickering emulsion template method according to claim 1, characterized in that The mass ratio of the emulsifier to ammonium perchlorate is 1:(10-10000).

4. The ammonium perchlorate complex according to claim 1, characterized in that It consists of a Pickering emulsion oil phase and a Pickering emulsion water phase; the Pickering emulsion oil phase consists of an emulsifier and a non-aqueous solvent; the Pickering emulsion water phase consists of ammonium perchlorate and water; The non-aqueous solvent is selected from one or more of ethyl acetate, dichloromethane and toluene.

5. The ammonium perchlorate complex based on the Pickering emulsion template method according to claim 4, characterized in that The volume ratio of the Pickering emulsion oil phase to the Pickering emulsion water phase is (1-5): (1-5).

6. The ammonium perchlorate complex based on the Pickering emulsion template method according to claim 1, characterized in that The particle size of the nano metal oxide is 10-30nm.

7. A method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method according to any one of claims 1 to 6, characterized in that: The method comprises: ultrasonically dispersing a non-modified emulsifier or a modified emulsifier in a non-aqueous solvent to obtain a Pickering emulsion oil phase; dissolving ammonium perchlorate in water to obtain a Pickering emulsion water phase; mixing the Pickering emulsion oil phase and the Pickering emulsion water phase, and emulsifying at an emulsification rate of 15000-20000 rpm for 2-3 minutes to obtain an ammonium perchlorate complex.

8. The method for synthesizing an ammonium perchlorate complex based on a Pickering emulsion template method according to claim 7, wherein: The preparation process of the modified emulsifier includes: ultrasonically dispersing a non-modified emulsifier in a solvent to obtain an emulsifier dispersion; dissolving a modifier in a solvent at 40 to 70° C. to obtain a modifier solution, wherein the modifier is stearic acid or a silane coupling agent; mixing the emulsifier dispersion with the modifier solution, reacting at 40 to 70° C. for 1 to 3 hours, and obtaining a modified emulsifier after centrifugation and washing.

9. The method for synthesizing an ammonium perchlorate complex based on the Pickering emulsion template method according to claim 8, characterized in that: The solvent is ethanol.

10. Use of the ammonium perchlorate complex based on the Pickering emulsion template method as claimed in any one of claims 1 to 6 as an oxidant to partially replace ammonium perchlorate in composite propellants.